2016
DOI: 10.1186/s12909-016-0552-1
|View full text |Cite
|
Sign up to set email alerts
|

Attributions, future time perspective and career maturity in nursing undergraduates: correlational study design

Abstract: BackgroundCareer maturity is an important parameter as nursing undergraduates prepare for their future careers. However, little is known regarding the relationships between attributions, future time perspective and career maturity among nursing undergraduates. The purpose of this study was to investigate the degree of career maturity and its relationship with attributions and future time perspective.MethodsA cross-sectional survey was designed. This survey was administered to 431 Chinese nursing undergraduates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 53 publications
1
16
0
5
Order By: Relevance
“…In line with the findings of our research, Cheng, Yang, Chen, Zou, Su, and Fan [47] found that FTP significantly affected career maturity. In career maturity, there is a dimension called career decisiveness [48].…”
Section:  Issn: 2252-8822supporting
confidence: 91%
“…In line with the findings of our research, Cheng, Yang, Chen, Zou, Su, and Fan [47] found that FTP significantly affected career maturity. In career maturity, there is a dimension called career decisiveness [48].…”
Section:  Issn: 2252-8822supporting
confidence: 91%
“…One of the theoretical concepts that most frequently used to evaluate an individual's readiness in entering the world of work is career maturity [11,12]. It is an essential factor for career preparedness in the twenty-first century [3]. Career is not something that goes into process suddenly or runs by itself for it is, instead, a picture of the future that uses as constructs one's past achievements and lifelong competence development [5].…”
Section: Introductionmentioning
confidence: 99%
“…Taber and Blankemeyer 2015). The way how individuals perceive their future can influence their career decisions, career maturity (Cheng et al 2016), job satisfaction (Weikamp and Göritz 2016), occupational self-efficacy, career commitment and turnover intention (Park and Jung 2015). However, there is a lack of research in how constraining job factors such as negative life events and hindering job demands impact employees' future time perspective (Rudolph et al, 2018).…”
mentioning
confidence: 99%